Passports for Sale: The Political Economy of Conflict and Cooperation in a Meta-Club - Kai A. Konrad; Ray Rees (Institute of Labor Economics (IZA), 2019)
Some of the member states of the European Union sell citizenship or residence to wealthy foreign investors. We analyse these "golden-passport" programs as a study in the political economy of conflict and cooperation in an international meta-club. Seen through the lens of club goods theory, the EU is a club of nations, each of which can be interpreted as itself a club. Each single nation reserves the right to govern the admission of new individual members into its own club, and new members automatically benefit from the EU wide meta-club good. We characterize the unique equilibrium when individual clubs that may differ in membership size are free to choose the terms on which they admit members, and evaluate it from the point of view of the wellbeing of the set of clubs as a whole. We identify club size and benefits as well as differences in cost externalities as the key determinants. We also consider how the set of clubs as a whole can respond to the economic inefficiency problems such a situation creates.
Keywords: F15; F53; H77; 330; club of clubs; membership rights; European Union; quotas